Análise granulométrica do compósito cimentício produzido com adição de resíduos de madeira e escória - Dinhane, Fernanda Christiane Rossetto [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Since the early twenty-first century, the construction sector has been the second largest on the rise in the Brazilian industrial sector, with a growth of 1.4% in 2012, and is likely to remain at this level for a long time. However, unlike decades ago, the industry has been seeking in its manufacturing process, sustainable materials, encompassing in their works the concept of sustainability. Thus, the timber sector seeks to satisfy a market increasingly demanding, innovating techniques and utilization being less aggressive to the environment. The purpose of this study was to produce and evaluate the mechanical strength of the composite cement with the addition of wood residues and slag low oven. Therefore, it was made 42 specimen cement-slag-wood, carried out in two steps. Since at the first, it was varied only the slag particle size, and at the second, through the best result of the previous step, it was varied the wood particles granulometry. The mechanical performance of the composite was evaluated by the results obtained in the compression test and the physical test for determining the density of the material. In the first step of the process can be concluded that the best result was achieved with the use of slag particles retained on the 60 mesh sieve. In the second phase of the study concluded that the best results were achieved with wood particles with the large particles, i.e. particles retained on the 10 mesh sieve. Both in the first and in the second step it can be seen that there has been the influence of the particle size of the waste materials. With the obtained results, could be evaluated that the use of waste for the production of cement-slag-wood composite showed lower performance when compared to the results obtained in studies without the use of waste. However, some applications are feasible to be performed with the use of composite wood-cement-slag

Desde o início do século XXI o setor da construção civil é vem sendo o segundo maior segmento em ascensão industrial no Brasil, com um crescimento de 1,4% em 2012, e tende a permanecer neste patamar por um longo tempo. Entretanto, diferente de décadas atrás, o setor busca em seu processo fabril, materiais sustentáveis, englobando em suas obras o conceito da sustentabilidade. Sendo assim, o setor madeireiro procura satisfazer um mercado cada vez mais exigente, inovando técnicas de aproveitamento de resíduos e sendo menos agressivo ao meio ambiente. A proposta deste estudo foi produzir e avaliar a densidade e a resistência mecânica do compósito cimentício com adição de resíduos de madeira e escória de baixo forno. Para tanto, confeccionou-se 42 corpos de prova de cimento-escóriamadeira, estudo realizado em duas etapas. Sendo que na primeira, variou-se apenas a granulometria da escória; e na segunda, através do melhor resultado da etapa anterior, variou-se à granulométrica do resíduo de madeira. O desempenho mecânico do compósito foi avaliado através dos resultados obtidos no teste físico e de compressão e no teste físico para a determinação da densidade aparente do material. Na primeira etapa do processo pode-se concluir que o melhor resultado foi conseguido com a utilização de partículas de escória retidas na peneira de 60 mesh. Já na segunda etapa do estudo concluiu-se que os melhores resultados foram conseguidos com as partículas de madeira de maior granulometria, ou seja, partículas retidas na peneira de 10 mesh. Tanto na primeira etapa como na segunda pode-se verificar que houve a influência da granulometria dos resíduos utilizados no desempenho do compósito. Com os resultados obtidos pode-se avaliar que o aproveitamento de resíduos para a produção do compósito cimentício apresentou desempenho inferior quando comparado aos resultados obtidos em estudos sem a utilização de resíduos...
Keywords: Materiais compostos; Resíduos; Particulas; Escoria; Cimento; Madeira; Eucalipto; Composite materials